Initiating a Collection Development Policy for Kumasi Polytechnic Library - Atta-Obeng, H. (Ghana Library Journal, 2007)
Collection development involves the activities of collection evaluation, selection of new materials, replacement of lost or damaged stock, deselection of older stock for either transfer to storage or disposal, and the handling of gifts. The aim of this article is to put together a collection development policy which will guide the development and management of the Kumasi Polytechnic Library’s collection. The collection development policy outlines the current principles, policies and practices that inform the selection, maintenance, access and retrieval of information resources both print and non print. It intimates that this policy is a living document which has to be reviewed and updated as the library’s collection needs change.